Fostering Pedagogical Excellence: Theoretical Foundations for Designing a Teaching Module on Chinese Ancient Poetry Art Songs for Undergraduate Students in China - Yu, Chen; Abdullah, Mohd Hassan (Grenek: Jurnal Seni Musik, 2024)
This paper explored the fundamental theoretical aspects involved in creating a comprehensive teaching module tailored for undergraduate students in China, with a specific emphasis on Chinese ancient poetry art songs. The process of constructing an effective teaching module was intricate, demanding a thorough exploration of various models and educational theories that laid the foundation for its development. The paper offered an overview of the theoretical framework employed in this undertaking, incorporating the ADDIE Model and key educational theories such as Jean Piaget's Constructivist Theory, Lev Vygotsky's Sociocultural Theory, and Howard Gardner's Multiple Intelligences. The ADDIE Model provided a structured approach to module development, guiding the systematic design, implementation, and evaluation phases to ensure that teaching materials were well-organized, efficient, and adaptable to diverse learning environments. Furthermore, the paper delved into the educational theories influencing the design of the teaching module. Piaget's Constructivist Theory emphasized active learning through hands-on experiences, Vygotsky's Sociocultural Theory underscored the role of social interaction and cultural context in learning, emphasizing collaborative learning experiences, and Gardner's Multiple Intelligences theory recognized the diversity of students' cognitive strengths, emphasizing the need for varied instructional strategies to cater to different learning styles. Through the integration of these theoretical foundations, this research aimed to develop a comprehensive, engaging, and effective educational resource tailored to the unique needs and learning preferences of students. The anticipated outcome of the teaching module was to enable educators to cultivate a greater understanding and appreciation of Chinese ancient poetry art songs among students.